URGENSI PENGATURAN GRATIFIKASI SEKSUAL SEBAGAI SALAH SATU BENTUK TINDAK PIDANA KORUPSI - Sitohang, Bertrand Silverius; Ghozali, Elizabeth; Marbun, Jaminuddin (LPPM Universitas Darma Agung, 2020)
Research on the urgency of regulating sexual gratification as a form of corruption is aimed at identifying whether or nor a gift can be given to attempt the sexual service received by civil servant or state officials categorized as gratuities related to corruption. In addition this study also aims at finding out and analyzing policies on sexual gratification in Law Number 31 of 1999 in conjuction with law number 20 of 2001 concerning eradication of corruption in Indonesia in the futer (ius contituendum) and finding out the urgency of regulating sexual gratification as a form of corruption. Based on research conducted, it can be seen that the provision of sexual service to civil servants or state administrators has fulfilled the elements of Article 12 B of Law Number 20 of 2001 concerning Corruption Crime. Providing gratuities in the form of sex service is against the law that lives in the community. Criminal law policy towards the eradication of sexual gratification in Indonesia can be seen in Law Number 31 of 1999 concerning eradicating Criminal Acts of Corruption in conjuction with Law Number 30 of 2002 concerning the Corruption Eradication Commission. Both of these laws have also been enacted Law Number 7 of 2006 concerning Ratification of the 2003 UN Anti-Corruption Convention. The urgency of regulating sexual gratification as a form corruption is based on the fact that in Indonesia the provison of sex services as a criminal act of corruption has occurred, making it easier to prove the efforts made by the KPK (Corruption Eradication Commission) in cases of sexual gratification by official country